Danlou Tablets Inhibit Atherosclerosis in Apolipoprotein E-Deficient Mice by Inducing Macrophage Autophagy: The Role of the PI3K-Akt-mTOR Pathway - Liu, Chunping; Chen, Guiling; Chen, Yanfen; Dang, Yue; Nie, Guangning; Wu, Dinghong; Li, Jinhua; Chen, Zide; Yang, Hailong; He, Dongyue; Li, Xiong; Sun, Jingbo; et al. (Frontiers in Pharmacology, 2021)
Atherosclerosis (AS) is a type of chronic vascular disease, and its etiology is not yet fully understood. AS is characterized by lipid deposition, atherosclerotic plaque formation, vascular stenosis or even complete blockage of the blood vessel wall. Clinical studies have shown that Danlou tablets (DLTs) can improve the heart function, quality of life, and prognosis of patients with coronary heart disease and myocardial infarction. However, its mechanism of action remains unknown. Our study revealed that DLTs ameliorated ApoE-/-AS mouse aortic atherosclerotic plaques [hematoxylin-eosin (HE) staining and small animal ultrasound] and reduced CD68+ macrophage infiltration, the expression of the inflammatory factor interferon-gamma (IFN-γ), vascular smooth muscle α-actin, and serum lipid levels. In vitro, in the macrophage foaming model, DLTs partially restored the activity of RAW264.7 cells, reduced the uptake of lipid droplets, and inhibited lipid droplet accumulation and apoptosis within BMDMs. We also found that Torin1, an autophagy agonist, reduced intracellular lipid deposition in BMDMs, as did DLTs. Moreover, DLTs upregulated the expression of the autophagy-related protein LC3II and decreased p62 accumulation in RAW264.7 cells. DLTs also inhibited the phosphorylation of p-PI3K, p-AKT, and p-mTOR, leading to upregulated autophagy in RAW264.7 cells. In summary, our results suggested that DLTs can promote autophagy in macrophages by inhibiting the PI3K/AKT/mTOR signaling pathway, thereby reducing foam cell formation and improving atherosclerosis.